تطوير وسيلة تعليم اللغة العربية على مادة البيانات الشخصية باستخدام كانفا وبيكسلاب لطلاب الصف العاشر: Pengembangan Media Pembelajaran Bahasa Arab Materi Al Bayanat Asy Syakhshiyyah Menggunakan Canva dan Pixellab pada Siswa Kelas X - Kadir, Huron Mahsyurah; Andi Arif Pamessangi (Al Ibrah: Journal of Arabic Language Education, 2024)
This study aims to identify the development process and the validity level of the developed product. This type of research is research and development (R&D) by adapting the 4D development model, which consists of four stages: define, design, develop, and disseminate. The subjects of this study are tenth-grade students of MAN Palopo. Data collection techniques include observation, interviews, validation sheets, student response questionnaires, and documentation. The data were analyzed using qualitative and quantitative data analysis techniques. The result of this development research is an Arabic learning media on the topic of "al-bayanaat asy-syakhsiyyah" using Canva and Pixellab applications for tenth-grade students of MAN Palopo. The product validation test results showed that: 1) the material expert validation scored 81.81%; 2) the media expert validation scored 88.88%; and 3) the learning expert validation scored 89.41%. Based on the product validation test results by the three expert validators, it shows that the "al-bayanaat asy-syakhsiyyah" material using Canva and Pixellab applications is highly valid for implementation in Arabic learning. يهدف هذا البحث إلى تحديد عملية التطوير ومستوى صلاحية المنتج المطور. نوع البحث هو البحث والتطوير (R&D)  باستخدام نموذج تطوير 4D الذي يتكون من أربع مراحل وهي مرحلة التحديد، والتصميم، والتطوير، والانتشار. وحدات البحث هم طلبة الصف العاشر بالمدرسة العالية الحكومية فالوفو.وأساليب جمع البيانات المستخدمة هي الملاحظة والمقابلة وأوراق التحقق من الصحة واستبانات استجابة الطلبة والوثائق. وتم تحليل البيانات باستخدام أساليب تحليل البيانات الكيفية والكمية. نتائج هذا البحث التطويري هي وسيلة تعليم اللغة العربية على مادة البيانات الشخصية باستخدام Canva وPixellab  لطلبة الصف العاشر في المدرسة العالية الحكومية فالوفو. تظهر نتائج اختبار التحقق من صحة المنتج ما يلي: 1) حصل اعتماد خبير المواد على درجة 81.81%؛ 2) حصل خبير الإعلام على درجة 88.88%؛ 3) وحصلت صدقية التعلم الخبير على درجة 89.41%. بناءً على النتائج، يمكن استنتاج أن وسيلة التعليم المطورة صالحة جداً للتطبيق في تعليم اللغة العربية.